How reliable are the available models for predicting the FRP contribution for the shear resistance of RC beams? - Sas, Gabriel (2008)
The performance of the most well-known models for the prediction of the contribution of FRP systems for the EBR shear strengthening of reinforced concrete beams is compared in this paper. The comparison was made using experimental results collected in a large database consisting of approximately 200 FRP strengthened concrete beams with various strengthening configurations and geometric dimensions. The results are not promising and a large scatter between the considered models was obtained. In addition, none of these models predict the ultimate shear capacity very accurately, which is of serious concern considering that some of the models are used in various design codes.